1981
DOI: 10.1111/j.1440-1819.1981.tb00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging in the Neuropil of Cerebral Cortex– A Quantitative Ultrastructural Study

Abstract: Six age groups, each composed of four animals from each of the following ages, were used to assess age-related ultrastructural changes in the neuropil of the 111 layer of the frontal cortex in rats: 3, 6, 12, 18, 24 and 30 months old. Random samplings within the neuropil were taken to produce 40 electron micrographs in each rat (totaling 960). The profiles of axon terminals, dendrites and astroglial processes in the neuropil of each micrograph were traced. Then the percentage of their areas for the area of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In gray matter, “stick” fractions between 10 and 20% are consistent with previous findings . However, the findings are not consistent with interpreting “sticks” as neurites, because the combined (neurite) density of axons and dendrites is approximately 60% according to histology . We hypothesize, as in Lampinen, that this discrepancy is due to dendrites not exhibiting "stick‐like" diffusion, due to, for example, exchange with soma or between short segments with different orientations.…”
Section: Discussionsupporting
confidence: 61%
“…In gray matter, “stick” fractions between 10 and 20% are consistent with previous findings . However, the findings are not consistent with interpreting “sticks” as neurites, because the combined (neurite) density of axons and dendrites is approximately 60% according to histology . We hypothesize, as in Lampinen, that this discrepancy is due to dendrites not exhibiting "stick‐like" diffusion, due to, for example, exchange with soma or between short segments with different orientations.…”
Section: Discussionsupporting
confidence: 61%
“…If this is the case, their respective prevalence should contribute similarly to microscopic diffusion anisotropy in the brain, and we would expect a contrast in MK A that bears similarity to the contrast in neurite density. In cortical gray matter, histology studies in mice have reported a rather even split between axons and dendrites and a neurite volume fraction of approximately 60% (Braitenberg & Schüz, ; Chklovskii, Schikorski, & Stevens, ; Ikari & Hayashi, ). In white matter, histology studies have reported a neurite density (intra‐axonal volume fraction) of 30–50% in the corpus callosum of macaque (Stikov et al, ) and mice (Jelescu et al, ) and in the rat spinal cord (Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In cortical gray matter, histology studies in mice have reported a rather even split between axons and dendrites and a neurite volume fraction of approximately 60% (Braitenberg & Schüz, 1998;Chklovskii, Schikorski, & Stevens, 2002;Ikari & Hayashi, 1981). In white matter, histology studies have reported a neurite density (intra-axonal volume fraction) of 30-50% in the corpus callosum of macaque (Stikov et al,FIGURE 4 Compartment densities could be estimated independently from T2 relaxation in white matter lesions, but not in the healthy brain.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, areas located in the frontal and temporal cortex show a strong correlation of grey matter thickness and functional activation with IQ scores: individuals with high IQ show larger grey matter volume of, for instance, Brodmann areas 21 and 38 (Choi et al 2008;Deary et al 2010;Karama et al 2009;Narr et al 2007). Cortical grey matter consists for a substantial part of dendrites (Chklovskii et al 2002;Ikari & Hayashi 1981), which receive and integrate synaptic information and strongly affect functional properties of neurons (Bekkers & Häusser 2007;Eyal et al 2014;Vetter et al 2001). Especially high-order association areas in temporal and frontal lobes in humans harbor pyramidal neurons of extraordinary dendritic size and complexity (Elston 2003;Mohan et al 2015) that may constitute variation in cortical thickness, neuronal function, and ultimately IQ.…”
Section: Introductionmentioning
confidence: 99%
“…IQ scores positively correlate with dendritic structure of temporal cortical pyramidal cells Cortical association areas in temporal lobes play a key role in high-level integrative neuronal processes and its superficial layers harbor neurons of increased neuronal complexity (DeFelipe et al 2002;Elston 2003;Scholtens et al 2014;van den Heuvel et al 2015). In rodents, the neuropil of cortical association areas consists for over 30% of dendritic structures (Ikari & Hayashi 1981). To test the hypothesis that human temporal cortical thickness is associated with dendrite size, we used 72 full reconstructions of biocytin-labelled temporal cortical pyramidal neurons from human layer 2, 3 and 4 part of which was previously reported (Mohan et al 2015 Figs 1&2).…”
mentioning
confidence: 99%